Clinical manual of contact lenses - Bennett, Edward S.; Henry, Vinita Allee (Philadelphia Wolters Kluwer/Lippincott Williams & Wilkins, 2014)
Designed to be used as a quick reference, this text allows readers to easily find the topic and information they need without having to search through an entire chapter to find it. Rigid gas permeable lens design and fitting, soft lens problem-solving, astigmatic management, and bifocal correction are just a few of the subjects covered in this manual. Each chapter includes sample cases to reinforce and demonstrate the practical nature of the topic, with nomograms and proficiency checklists summarizing and emphasizing the important points. With this guide, students and practitioners will have a dependable resource to help fit, evaluate, and troubleshoot any contact lenses, especially specialty designs for years to come.
Preliminary evaluation -- Optical considerations in contact lens practice -- Corneal topography -- Gas-permeable material selection -- Lens design, fitting, and evaluation -- Gas-permeable lens care and patient education -- Verification of gas-permeable lenses -- Gas-permeable lens problem solving -- Modification of gas-permeable lenses -- Soft lens selection, fitting, and evaluation -- Soft lens fitting and evaluation -- Soft lens care and patient education -- Soft lens problem solving -- Correction of astigmatism -- Bifocal contact lenses -- Overnight contact lens wear -- Aphakia -- Children and contact lenses -- Keratoconus -- Postsurgical contact lens fitting -- Scleral lenses -- Orthokeratology -- Management of contact lens-associated or lens-induced pathology -- Contact lens practice management.
'Online access to fully searchable text & instructor PowerPoint presentations'--Cover.
This book includes online access at http://solution.lww.com, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Contact lenses